Translatio Imperii: The Old English Orosius and the Rise of Wessex - Leneghan, F (Walter de Gruyter GmbH, 2015)
This article argues that the Old English Orosius, a work traditionally viewed as a product of the educational reforms of King Alfred of Wessex (r. 871- 899), can be constructively read in relation to developments in Anglo-Saxon political thought in the early tenth as well as in the late ninth centuries. The earliest extant manuscript of the Orosius was probably copied at Winchester in the early tenth century by the same scribe responsible for the entries for the late ninth and early tenth century in MS A of the Anglo-Saxon Chronicle. This section of the Chronicle charts both the break-up of the Carolingian empire and the conquests of Alfred and his successors, Edward the Elder and Æthelstan, over various kings and peoples of Britain. Treating the reports of Ohthere and Wulfstan contained in the geographical preface to the Orosius as an integral part of the text as it was read in the early tenth century, rather than as an extraneous interpolation, I suggest that this passage invites readers to consider the rapidly expanding West Saxon kingdom in relation to the great empires which preceded it. I then outline how the translator refashioned Orosius’s ‘universal history’ into a work of imperial history which is more directly concerned with Rome’s long and difficult rise than with its fall to the Goths in 410. I conclude that the Orosius might have encouraged early tenth-century Anglo-Saxon readers to interpret the recent rise of Wessex to overlordship in Britain as part of an ongoing process of translatio imperii, the transference or succession of empires, contingent on the Christian virtue of its rulers.